Co-gasification of thermally pretreated wheat straw with Shengli lignite for hydrogen production. (March 2018) - Yang, Xiaoqin; Liu, Xuejing; Li, Rui; Liu, Chuang; Qing, Tao; Yue, Xiaoming; Zhang, Shuangquan
Abstract: Wheat straw (WS) was thermally pretreated at 200, 300 and 400 °C in a muffle furnace, respectively, before co-gasified with Shengli lignite (SL). The results from thermogravimetric analyzer (TGA) experiments showed that interaction of solid phases between SL and the pretreated WSs occurred at the gasification stage rather than the pyrolysis stage and the synergy varied with the biomass pretreatment temperature. Co-gasification of WS-200/SL had an inhibitory effect, and there was no synergy effect during WS-300/SL co-gasification. In contrast, co-gasification of WS-400/SL had a positive effect in the gasification stage. The investigation of co-gasification in a fixed-bed reactor, however, found synergies in product gas yields and carbon conversion for both WS-200/SL and WS-400/SL. The (H2 +CO) yield and carbon conversion increased by 3.95% and 18.32%, respectively, for co-gasification of WS-400/SL blends compared with the calculated values based on individual materials. From the results of both the TGA and fixed-bed experiments, it is concluded that 400 °C of pyrolysis temperature for WS is the best to produce hydrogen for co-gasification with SL. The maximum synergetic effect was explained by the relatively high surface area and high content of alkali metals in WS-400. Graphical abstract: Image 1 Highlights: Raw wheat straw was thermally pretreated at 200, 300 and 400 °C. Co-gasification of pretreated wheat straw and lignite was studied in a TGA and a fix-bed reactor. Interactions or synergistic effects between the blends vary with the pretreatment temperature. Significant increases in (H2 +CO) yield and carbon conversion are observed when wheat straw is pretreated at 400 °C.